2014
DOI: 10.1371/journal.pone.0101487
|View full text |Cite
|
Sign up to set email alerts
|

Green Manure Addition to Soil Increases Grain Zinc Concentration in Bread Wheat

Abstract: Zinc (Zn) deficiency is a major problem for many people living on wheat-based diets. Here, we explored whether addition of green manure of red clover and sunflower to a calcareous soil or inoculating a non-indigenous arbuscular mycorrhizal fungal (AMF) strain may increase grain Zn concentration in bread wheat. For this purpose we performed a multifactorial pot experiment, in which the effects of two green manures (red clover, sunflower), ZnSO4 application, soil γ-irradiation (elimination of naturally occurring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 45 publications
1
50
2
1
Order By: Relevance
“…This relationship between soil health and human health has been documented (Kemper & Lal, 2017;Pepper, 2013;Wrench, 1939), and human management can make a considerable difference to the soil properties that influence soil health (Parras-Alcántara, Lozano-García, Keesstra, Cerdà & Brevik, 2016). For example, it has been reported that (a) soil managed in a way that produced higher soil health indicators can produce better quality strawberries, with greater nutritional value to support human health, than soil with lower health indicators (Reganold et al, 2010), (b) using cover crops to enhance microbial activity increases zinc uptake in wheat (Aghili et al, 2014) and (c) organic compost can reduce the uptake of cadmium in rice (Liu, Chen, Cai, Liang & Huang, 2009). However, it should be noted that a definitive link between soil health and the nutritional quality of food has not been conclusively established, as a review of the available literature showed mixed results (Reeve et al, 2016).…”
Section: Soil Healthmentioning
confidence: 99%
“…This relationship between soil health and human health has been documented (Kemper & Lal, 2017;Pepper, 2013;Wrench, 1939), and human management can make a considerable difference to the soil properties that influence soil health (Parras-Alcántara, Lozano-García, Keesstra, Cerdà & Brevik, 2016). For example, it has been reported that (a) soil managed in a way that produced higher soil health indicators can produce better quality strawberries, with greater nutritional value to support human health, than soil with lower health indicators (Reganold et al, 2010), (b) using cover crops to enhance microbial activity increases zinc uptake in wheat (Aghili et al, 2014) and (c) organic compost can reduce the uptake of cadmium in rice (Liu, Chen, Cai, Liang & Huang, 2009). However, it should be noted that a definitive link between soil health and the nutritional quality of food has not been conclusively established, as a review of the available literature showed mixed results (Reeve et al, 2016).…”
Section: Soil Healthmentioning
confidence: 99%
“…In addition, green manure reduces weed incidence and soil pathogens by increasing beneficial microorganisms, as well as controlling disease-causing pathogens in potato (Davis et al, 2010, Larkin et al, 2010, Himmelstein et al, 2014. This contributes to a better growth condition of the crop, greater absorption of other soil nutrients and an increase in productivity (Aghili et al, 2014, Campiglia et al, 2009, and the sustainability of cropping systems (St Luce et al, 2015). Green manure at 400 Kg ha -1 and 200 Kg ha -1 of C. juncea increases the accumulation of dry matter in potato shoots and tubers.…”
Section: Total and Commercial Productivity Of Potatomentioning
confidence: 99%
“…The positive effects of green manuring on open-field vegetables are well documented (Beckmann, 1977;Chaves et al, 2004;MacRae and Mehuys, 1985;Stirling and Stirling, 2003;Thorup-Kristensen, 2006) and followed by modern greenhouse applications (Aghili et al, 2014;Duyar et al, 2008;Rose et al, 2015;Tüzel et al, 2013). Here, the angiosperm Sorghum vulgare used in greenhouse cultivations is suggested as green manure through crop rotation with tomato plants.…”
Section: Technology 2 (T2): Crop Rotation For Green Manuring In Greenmentioning
confidence: 99%